Marsya Iwani Syahirah, new UMPSA student, continues her studies in engineering technology - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 8 March 2025 – Marsya Iwani Syahirah Mohd Izwan is a new student at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and will be pursuing her Bachelor of Engineering Technology (Energy and Environment) with Honours. Marsya, the second of three siblings, is now stepping into university life after completing her diploma studies.